Particles Containing Cells as a Strategy to Promote Remyelination in Patients With Multiple Sclerosis - Matías-Guiu, Jorge; Matías-Guiu, Jordi A.; Montero-Escribano, Paloma; Barcia, Juan A.; Canales-Aguirre, Alejandro A.; Mateos-Diaz, Juan C.; Gómez-Pinedo, Ulises (Frontiers in Neurology, 2020)
The repair of demyelinated lesions is a key objective in multiple sclerosis research. Remyelination fundamentally depends on oligodendrocyte progenitor cells (OPC) reaching the lesion; this is influenced by numerous factors including age, disease progression time, inflammatory activity, and the pool of OPCs available, whether they be NG2 cells or cells derived from neural stem cells. Administering OPCs has been proposed as a potential cell therapy; however, these cells can only be administered directly. This article discusses the potential administration of OPCs encapsulated within hydrogel particles composed of biocompatible biomaterials, via the nose-to-brain pathway. We also discuss conditions for the indication of this therapy, and such related issues as the influence on endogenous remyelination, migration of OPCs to demyelinated areas, and the immune response, given the autoimmune nature of multiple sclerosis. Chitosan and derivatives constitute the most promising biomaterial for this purpose, although these issues must be addressed. In conclusion, this line of research may yield an alternative to the remyelinating drugs currently being studied.